The Process of Adjusting to Divorce After Leaving Violent Marriages: A Case Study of Iranian Women. Issue 7 (April 2021) - Nikparvar, Fatemeh; Stith, Sandra; Dehghani, Mohsen; Liang, Jia Grace
Despite growing international attention to Intimate Partner Violence (IPV), there is little systemic information available regarding the process of adjusting to divorce after leaving violent marriages among Iranian women. Despite the strong religious discouragement and social stigma associated with divorce in Iran, divorce has always been recognized as a possible outcome of marriage. This qualitative study was conducted to understand the process that nine Iranian women who left violent marriages went through after divorce. The data came from two interviews with each participant and interviewer's notes that were taken during the interview. The data were analyzed using phenomenology and themes related to adjusting to divorce after experiencing IPV were identified. The process of adjusting to divorce seemed to occur in phases, that is, "initial experience after divorce, " "searching for stability/challenges/resources, " and "the process of developing new identity but still not being at peace." Each phase consists of subthemes and boundaries between these phases were fluid and adjustment was an ongoing process. This process was a journey for these Iranian IPV victims, which was dependent on their financial situation, emotional support, having a child or not, and their psychological health. These findings can help Iranian women who are in the process of adjustment to divorce to make sense of their experience. Also, findings provide a framework for researchers and clinicians in their work with female survivors of violent marriages. By testing these findings, researchers will be able to develop a theory regarding healing and disentanglement process. Clinicians need to understand the role of internalized stigma and how they can help their clients who are seeking to adjust after leaving violent marriages in Iran to reduce internalized stigma of divorce and challenge some of negative cultural beliefs against divorced women. Implications and suggestions for future research and clinicians are provided.